Com o movimento das águas: práxis pedagógica da educação física em uma escola ribeirinha no amazonas - Lopes, Diana Baima (Brasil, 2022)
The riverside people, “people from the Amazonian countryside” live in communities far from the headquarters of their municipalities, sometimes separated by the course of water that moves differently in time and space. At this juncture, Rural Education articulates between pedagogical strategies and the dialectic of the community - which occurs through the process of rising (flood) and falling of the waters, a constant movement in which the teacher, students and the entire riverside community builds and rebuilds as relationships social. School Physical Education is the curricular component that deals with the most striking practices in their various manifestations and different purposes and thus we reflect the importance of School Physical Education for Integral Education. It is necessary to describe a unique reality of this territory as practices in physical education classes at the riverside countryside school. Therefore, the objective of this research, through the curriculum of Physical Education. This is a descriptive, qualitative study, being a case study, it will be carried out in the municipality of Manaus in the northern school of the Ebenezer community, Tarumãzinho, riverside - Rio Negro, in the state of Amazonas, region, Brazil. The scenario and a participant, being a Physical Education teacher at the school, were intentionally selected to fulfill the proposed objectives in. An individual interview technique was used, with the elaboration of a form with open and closed questions. Content analysis was performed, after reading and analyzing the interview, the results were grouped into two categories. After the results, it is concluded that: the riverine subject produces culture with characteristics that differ from each community; the need for discussion about the peculiarities of the riverside and road zone of Manaus and the inclusion of these educational guidelines and school plans; the existence of difficulties in diagnosing students with global learning diagnoses and diagnoses; drought is the period in the river that interferes most in the annual schedule of classes, to the detriment of access by boats. And the development of Higher Education of Institutions that researches, in depth, and its most varied dimensions of Rural Education in Amazonas.